Die regionale Entwicklung der USA in den achtziger Jahren: Bevölkerungsumverteilung und wirtschaftliche Umstrukturierung - De Lange, Norbert (ERDKUNDE, 1993)
During the 1980s the regional development of the USA was characterized by major changes in economic and population growth. At first sight the growth figures seem to reveal the same contrast as in the 1970s between the Northeast and the South and West. But in particular some significant differences can be outlined: New York was able to attract population again, whereas population stagnation implying substantial outmigration, existed in Ohio, Indiana, Illinois and Michigan. California, Florida and Texas were the most important winners of population in the West and in the South. Maryland, Virginia, North and South Carolina as well as Georgia represented the real growth regions in the South. But the population growth of Kentucky, Tennessee, Alabama, Arkansas, and Oklahoma was very small, Louisiana lost population, and even fell behind the population growth in the 1960s. With regard to growth expectations this development may be called an actual surprise of the spatial population development. The 1980s suggest some return to traditional urbanization patterns. Non-metropolitan growth levels decreased substantially while metropolitan growth increased. As a group large metropolitan areas had higher population profits than smaller areas. The economic development of the USA has been the basic reason for the different regional population changes. An economic restructuring has taken place characterized by deindustrialization, growth of high technology industries and growth in service industries.